Efeitos do treinamento resistido sobre o metabolismo lipídico, a inflamação e a morfometria do tecido adiposo de ratas ovariectomizadas - Stotzer, Uliana Sbeguen (2013)
Visceral obesity is an important risk factor cardiovascular diseases. After menopause, fat distribution shifts to visceral depots leading to lipid metabolism disorders and chronic lowgrade inflammation. Resistance training (RT) has beneficial effects in postmenopausal women, but its effectiveness in normalizing visceral adipose tissue disorders is not well understood. To address this questions adult female Sprague-Dawley rats were randomly divided into six groups (n=6 per group): sham-sedentary (SHAM), ovariectomized- sedentary (OVX), SHAM-trained (S-T), OVX-T. Sham or ovariectomy procedure was performed with 250 grams. Three weeks after the surgery, trained groups started 10 weeks of climbing in a 1.1-m vertical ladder with progressive load of 65%, 85%, 95% and 100% of rat s previous maximal overload. All animals were killed 92 days after being ovariectomized and trained animals were killed 48 hours after the last training session. Mesenteric, parametrial and subcutaneous adipose tissues were prepared for morphometric analyses in colidina and osmium tetroxide and part of mesenteric adipose tissue was stored for mRNA analyses by quantitative PCR. Resistance training prevented ovariectomy-induced higher body weight, food intake, feeding efficiency and mesenteric and subcutaneous, but not parametrial adipocyte area. In addition, RT avoided OVX-induced upregulation in the lipogenic genes PPAR-γ, SREBP-1c and its downstream targets SCD-1 and ACC gene expression. Further, RT increases the gene expression of mitochondrial β-oxidation enzyme CPT-1 in OVX rats. RT also prevented the chronic low-grade inflammation in OVX group, demonstrated by the presence of macrophage markers (F4/80 and CD11b), increase in activated Th1 cells (IFN-γ) and the proinflammatory cytokines (TNF-α, IL-1β and IL-6). RT additionally created an antiinflammatory (IL-10) environment. The present results reflect a powerful prophylactic effects of resistance training in preventing pathological effects of estrogen deficiency, both at physiological and molecular levels. Therefore, we suggest that this may be an advantageous low cost-effective treatment at post-menopausal phase, since appropriately prescribed.